Answer:
x+1 , x<-1
x²-bx-4 , -1≤x≤4
1/2 x +a
substitute x=-1 , continuous everywhere
x+1=x²-bx-4 when x=-1
-1+1=-1²-b-4
<h2>1+b-4=0 ⇒ +b-3 ⇒ b=3</h2>
then for :
x²-bx-4=1/2 x +a for x=4
4²-4b-4=1/2x+a
16-4(3)-4=4/2+a
16-12-4-2=a
<h2>a=-2</h2>
the equations will be :
x+1
x²-3x-4
1/2x-2
I hope this help
When we simplify (3 + √5)(3 + √2), the result obtained is:
9 + 3√2 + 3√5 + √10
<h3>Surd operation </h3>
a√b × c√d = (a × c)√(b × d)
<h3>How to simplify (3 + √5)(3 + √2)</h3>
(3 + √5)(3 + √2)
Expand by clearing the bracket
3(3 + √2) + √5(3 + √2)
9 + 3√2 + 3√5 + √10
Thus,
(3 + √5)(3 + √2) = 9 + 3√2 + 3√5 + √10
Learn more about surd:
brainly.com/question/24700530
#SPJ1
Answer:
What are you asking?
Step-by-step explanation:
Neisksnjshwjaksbsuskbdbskshthanksjdusbns
Answer:
77
Step-by-step explanation:
percentage Students
78%-------------- -273
100%-------------- ---X
(100x273)/78 = 350 students in class so
how many did not pass?
350-273 = 77 students not pass